Fabrication and characterization of net-shaped iron nitride-amine-epoxy soft magnetic composites - Hoyt, Melinda R.; Falcon, Gillian I.; Pearce, Charles J.; Delaney, Robert E.; Stevens, Tyler E.; Johnson, Emily M.; Szenderski, Thomas M.; Sorenson, Nathan R.; Fultz-Waters, Sydney F.; Rodriguez, Mark A.; Whalen, Lisa J.; Monson, Todd C. (Frontiers in Materials, 2023)
Soft magnetic composites (SMCs) offer a promising alternative to electrical steels and soft ferrites in high performance motors and power electronics. They are ideal for incorporation into passive electronic components such as inductors and transformers, which require a non-permanent magnetic core to rapidly switch magnetization. As a result, there is a need for materials with the right combination of low coercivity, low magnetic remanence, high relative permeability, and high saturation magnetization to achieve these goals. Iron nitride is an attractive soft magnetic material for incorporation into an amine/epoxy resin matrix. This permits the synthesis of net-shaped SMCs using a “bottom-up” approach for overcoming the limitations of current state-of-the-art SMCs made via conventional powder metal processing techniques. In this work we present the fabrication of various net-shaped, iron nitride-based SMCs using two different amine/epoxy resin systems and their magnetic characterization. The maximum volume loading of iron nitride reached was ∼77% via hot pressing, which produced SMCs with a saturation magnetic polarization (Js) of ∼0.9 T, roughly 2–3 times the Js of soft ferrites.